2006
DOI: 10.1063/1.2165180
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of iron core-shell nanoparticles on a H-terminated Si(100) surface

Abstract: Articles you may be interested inSurface-anisotropy and training effects of exchange bias in nanoparticles with inverted ferromagneticantiferromagnetic core-shell morphology Localized surface plasmon resonance enhanced magneto-optical activity in core-shell Fe-Ag nanoparticles J. Appl. Phys. 107, 09B303 (2010); 10.1063/1.3355905Effect of particle size on the magnetic properties of core-shell structured nanoparticles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 12 publications
4
38
0
Order By: Relevance
“…In our recent work involving electrodeposition in an FeCl 3 solution, the as-deposited oval-shaped nanorod Fe particles were found to consist of Fe cores with composite FeOOH and FeO shells, while the spherical NPs correspond to Fe cores with composite Fe 2 O 3 and FeO shells. 20 In the present cubic NP case, there is a sizable Fe 2p feature corresponding to metallic Fe before sputtering, which was not observed in the case of the oval-shaped nanorods and spherical NPs. This confirms that the oxide shell for the cubic NPs must be not only thinner than those of the oval-shaped nanorods and spherical NPs but also less than the escape depth of the Fe 2p photoelectron at 780 eV kinetic energy ͑ϳ6 nm͒.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In our recent work involving electrodeposition in an FeCl 3 solution, the as-deposited oval-shaped nanorod Fe particles were found to consist of Fe cores with composite FeOOH and FeO shells, while the spherical NPs correspond to Fe cores with composite Fe 2 O 3 and FeO shells. 20 In the present cubic NP case, there is a sizable Fe 2p feature corresponding to metallic Fe before sputtering, which was not observed in the case of the oval-shaped nanorods and spherical NPs. This confirms that the oxide shell for the cubic NPs must be not only thinner than those of the oval-shaped nanorods and spherical NPs but also less than the escape depth of the Fe 2p photoelectron at 780 eV kinetic energy ͑ϳ6 nm͒.…”
Section: Resultsmentioning
confidence: 63%
“…19 Recently, we reported the synthesis of near-monosized Fe oval-shaped nanorods ͑130 nm length ϫ 25 nm diameter͒, the so-called nanorice particles, and spherical NPs ͑6-40 nm diameter͒ by using electrodeposition on a H-Si͑100͒ ͑i.e., H-terminated͒ electrode at different FeCl 3 concentrations. 20 Although these Fe core-shell NPs could be deposited with well-defined shapes uniformly, a considerable amount of oxide shell was found, which consequently limited the observable magnetic properties of the Fe core itself. To date, it remains a big challenge to deposit a homogeneous layer of individual, welldefined nanostructured particles with significant Fe cores.…”
mentioning
confidence: 99%
“…At the end of the cyclic voltammogram, i.e., in the potential region of −900 to 0 mV, an anodic current is observed. As previously described, this anodic region can be assigned with oxidation of Fe to Fe 2+ and Fe 2+ to Fe 3+ (or Fe to Fe 3+ in some part) [22,24]. The reduction wave, as well as cathodic and anodic current peaks, becomes larger and more intense with addition of Co.…”
Section: Electrochemical Analysesmentioning
confidence: 90%
“…Zarpellon et al [22] reported that the Fe films electrodeposited on a Si(111) substrate exhibit submicrometer grains with slightly flat terraces on the surface, along with the presence of iron silicides. Lee et al [23] have shown that α-Fe(110) films with nearly monosized nanostructures of spherical shapes on an n-type Si(111) substrate could be grown by pulsed electrodeposition in a nonaqueous solution, and Zhao et al [24] reported the synthesis of near-monosized Fe oval-shaped nanorod particles and spherical nanoparticles using electrodeposition on a hydrogen-terminated Si(100) surface from aqueous FeCl 3 solutions. Although the Fe core-shell thin films and nanostructures can be deposited uniformly and with well-defined shapes, the influence of the considerable oxide shells is detrimental for their magnetic properties.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous techniques have been applied to fabricate TiO 2 films on glass, metal or ceramic substrates such as dip-coating, sol-gel, Langmuir-Blodgett technique, electrodeposition, and layer-by-layer deposition [4][5][6][7]. The fabrication of macro-/meso-porous TiO 2 or the introduction of silica component is usually required to improve the surface area and hydrophilicity for inorganic TiO 2 film [7][8][9].…”
Section: Introductionmentioning
confidence: 99%